The making of a mega-journal in taxonomy - Zhang, Zhi-Qiang (Zootaxa, 2006)
We live in an era of elevated rates of extinction, yet about 90% of the Earth’s species of animals, plants and micro-organisms remain undescribed (Wilson, 2004). Although there are many journals that may publish taxonomic papers, it is increasingly difficult to publish papers on descriptive taxonomy in a timely and cost-effective manner. It is common for a taxonomist to wait for eight to ten months and sometimes years to get a paper published. And unless there is access to an institutional monograph series, it is even more difficult to publish a large taxonomic revision or monograph, not only because of costs, but the fact that most journals are of a fixed size and have limits on the length of papers. This impediment in publishing has a huge negative impact on taxonomy—the delay and difficulty in getting works published can discourage taxonomists who worked for years and unpublished works are a huge waste of talent and resources (often publicly funded). Large monographs are particularly important to the study of complex species-rich taxa, as taxonomy is about comparison, and closely related species must be compared together. Much needed is a rapid and efficient journal for descriptive papers and monographs in taxonomy. Published concurrently in print and online, Zootaxa was established as a rapid journal at the start of this century to remove these impediments in taxonomy. It has received overwhelming support from zoological taxonomists around the world, despite the fact that this diverse group of specialists are often perceived as too individualistic and fragmented into diverse subdisciplines to come together as a community. Zootaxa rapidly transformed itself from a small journal publishing 20 papers totalling 302 pages on 15 occasions in 2001 to a mega-journal publishing 1,020 papers in 22,052 pages as frequently as twice each week in 2006 (Fig. 1)—a pattern of rapid growth that is unprecedented for any scholarly journal, in both the sciences and humanities. This is indeed a very promising sign for the rejuvenation of zoological branch of one of world’s oldest science (that of naming and describing nature) in a new era when its services are most needed.